Myocardial fibrosis during atrial fibrillation: histological and cardiographic predictors - R.F. Rakhmatullov; F.K. Rakhmatullov; N.A. Timofeeva (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2023)
Background. The formation of myocardial fibrosis is the leading mechanism for occurrence of atrial fibrillation (AF). In this regard, an attempt to prevent development of myocardial fibrosis and its treatment is pathogenetically expedient. In recent years, there have been reports on the early diagnosis of myocardial fibrosis using electrocardiography (ECG). Therefore, in order to understand the clinical significance of myocardial fibrosis, it is necessary to compare morphological and ECG parameters. The purpose of this work is to study the histological and cardiographic predictors of myocardial fibrosis in AF. Material and methods. The study includes 64 patients with ECG – documented AF, which divided into three groups. The first group includes 20 women aged 27-43 years, the 2nd group – 21 women aged 47-52 years, and the 3rd group – 23 women aged 54-68 years. ECG data compared with the prevalence of fibrosis in the left atrium, right atrium, and Bachmann's bundle. Results. It has been established that myocardial fibrosis slows down the conduction of excitation through the atria. The width of the atrial wave (P) at the age of 27-43 years is 137.1±1.7 ms, by the age of 47-52 years it increases by 7.2% (p<0.001), and by the age of 54-68 years – by 13 .8% (p<0.001). The relationship between the clinical manifestations of AF and the P wave width (p<0.001), P wave dispersion (p<0.001) and the width of the second phase of the P wave in lead V1 on the ECG (p<0.001) was shown. Results. It has been established that the area of myocardial fibrosis in AF increases with age. At the age of 27- 43 years, the fibrosis area is 17.8%, 47-52 years old – 24.3%, and at 54-68 years old – 26.1%. It was found that myocardial fibrosis in AF slows down the conduction of excitation through the atria. The width of the atrial wave (P) at the age of 27-43 years is 137.1±1.7 ms, by the age of 47-52 years it increases by 7.2% (p<0.001), and by the age of 54-68 years by 13, 8% (p<0.001). Atrial myocardial fibrosis was shown to be associated with P wave width (p<0.001), P wave dispersion (p<0.001) and P wave second phase width in lead V1 on ECG (p<0.001). Conclusions. Received data shows a close relation between the morphological structure and ECG signs of atrial myocardial fibrosis in AF.